A modified multiphase oscillator with improved phase noise performance. (April 2017) - Alberts, Antonie C.; Sinha, Saurabh
Abstract: This paper investigates the factors that influence the phase noise performance of an oscillator and proposes a modified structure for improved phase noise performance. A single and multiphase oscillator analysis using the harmonic balance method is presented. The modified structure increases the oscillation amplitude without increasing the bias current and leads to improved phase noise performance as well as decreased power consumption. The modification is analyzed and the figure of merit of the oscillator shows a significant improvement of 21 dB. Numerical and analytical solutions are presented to predict the oscillation frequency and phase noise. The analytical solution is used to approximate the first harmonic and can be combined with numerical simulations to extrapolate phase noise performance.